2021
DOI: 10.1002/cbdv.202100500
|View full text |Cite
|
Sign up to set email alerts
|

3‐Aminopyrazolo[3,4‐b]pyridine: Effective Precursor for Barium Hydroxide‐Mediated Three Components Synthesis of New Mono‐ and Bis(pyrimidines) with Potential Cytotoxic Activity

Abstract: In this study, an efficient one-pot procedure for preparing a new series of pyrazolo [3,4-b]pyridine-fused pyrimidines was described. The target hybrids were developed through a three-component reaction of 3-amino-1H-pyrazolo [3,4-b]pyridine, benzaldehydes, and acetophenones (molar ratio 1 : 1 : 1). The best conditions for the previous reaction were 2.5 equivalents of barium hydroxide in DMF at 150 °C for 6 h. New bis(pyrimidines) were synthesized in high yields using a similar one-pot reaction protocol with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…Recently, we discovered that bis‐analogs might display more effective bioactivity when compared to their mono‐analogs [3,33] . We compared the antibacterial activity of some new bis(1,3,4‐oxadiazoles) and their mono‐analogs in this study.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, we discovered that bis‐analogs might display more effective bioactivity when compared to their mono‐analogs [3,33] . We compared the antibacterial activity of some new bis(1,3,4‐oxadiazoles) and their mono‐analogs in this study.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we discovered that bis-analogs might display more effective bioactivity when compared to their mono-analogs. [3,33] We compared the antibacterial activity of some new bis(1,3,4-oxadiazoles) and their mono-analogs in this study. Experimental results showed that bis(1,3,4-oxadiazoles) 11 and their monoanalogs 13, which are linked to an additional 4-(2,5dimethyl-1H-pyrrol-1-yl) unit, was found to be more effective than that of bis(1,3,4-oxadiazoles) 6 and their mono-analogs 12.…”
Section: Biology 221 Evaluation Of Minimum Inhibitory Concentration (...mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the promising AChE inhibitory activity of pyrazole‐based scaffolds has been investigated in numerous reports [19–22] . The previous hybrids also have a wide range of other biological activities, such as antibacterial, [23] antifungal, [24] antiviral, [25] anti‐inflammatory, [26] anticancer, [27] and antimalarial activity [28] . Additionally, they can act as promising inhibitors of HIV‐1, [29] and EGFR, [30] as well as COX‐2, [31] and MurB enzymes [32] .…”
Section: Introductionmentioning
confidence: 99%